Ionic conductivity of Na3Al2P3O12 glass electrolytes role of charge compensators - Keshri, Shweta R.; Ganisetti, Sudheer; Kumar, Rajesh; Gaddam, Anuraag; Illath, Kavya; Ajithkumar, Thalasseril G.; Balaji, Sathravada; Annapurna, K.; Nasani, Narendar; Krishnan, N. M. Anoop; Allu, Amarnath R. (Inorganic Chemistry, 2021)
In glasses, a sodium ion (Na+) is a significant mobile cation that takes up a dual role, that is, as a charge compensator and also as a network modifier. As a network modifier, Na+ cations modify the structural distributions and create nonbridging oxygens. As a charge compensator, Na+ cations provide imbalanced charge for oxygen that is linked between two network-forming tetrahedra. However, the factors controlling the mobility of Na+ ions in glasses, which in turn affects the ionic conductivity, remain unclear. In the current work, using high-fidelity experiments and atomistic simulations, we demonstrate that the ionic conductivity of the Na3Al2P3O12 (Si0) glass material is dependent not only on the concentration of Na+ charge carriers but also on the number of charge-compensated oxygens within its first coordination sphere. To investigate, we chose a series of glasses formulated by the substitution of Si for P in Si0 glass based on the hypothesis that Si substitution in the presence of Na+ cations increases the number of SiOAl bonds, which enhances the role of Na as a charge compensator. The structural and conductivity properties of bulk glass materials are evaluated by molecular dynamics (MD) simulations, magic angle spinning-nuclear magnetic resonance, Raman spectroscopy, and impedance spectroscopy. We observe that the increasing number of charge-imbalanced bridging oxygens (BOs) with the substitution of Si for P in Si0 glass enhances the ionic conductivity by an order of magnitudefrom 3.7 x 10(-8) S.cm(-1) to 3.3 x 10(7) S.cm(-1) at 100 degrees C. By rigorously quantifying the channel regions in the glass structure, using MD simulations, we demonstrate that the enhanced ionic conductivity can be attributed to the increased connectivity of Na-rich channels because of the increased charge-compensated BOs around the Na atoms. Overall, this study provides new insights for designing next-generation glass-based electrolytes with superior ionic conductivity for Na-ion batteries